Analysis of Optimum Asphalt Content of Lasbutag Mixture (Buton Aggregate Asphalt Coating) Modified by Waste Oil and Diesel as Modifier - Wintari, Ni Kadek; Desi, Natsar; Gusty, Sri (ASTONJADRO, 2024)
Asbuton, a natural asphalt source on Buton Island in Southeast Sulawesi, is one of Indonesia's potential sources of natural wealth. As a road pavement material, LASBUTAG still has many weaknesses. This is especially true for cold LASBUTAG mixtures, which are only suitable for highways with light traffic. To mix Asbuton in cold conditions, a modifier is needed, the data of which is rare on the market, so other alternatives need to be considered as a modifier. In this research, we will try to use a mixture of waste oil and diesel as a modifier. The use of waste oil in this research is by looking at the development of the volume of waste oil. which continues to increase along with the increase in the number of motorized vehicles and motorized machines. The spread of oil waste is very widespread from big cities to rural areas throughout Indonesia. Waste from lubricating oil is included in B3 waste which needs special treatment in its processing. The aim of this research is to analyze the optimum asphalt content of cold Lasbutag mixtures with modifier materials from waste oil and diesel. From the results of this research, the Optimum Asphalt Content (KAO) in the Lasbutag Wearing Course (WC) mixture was 6.30% of the total mixture weight. Based on regression analysis, asphalt content can produce stability of 704.464 kg, flow of 3.078 mm, Vim of 4.467%, VMA of 17.077% and IKS of 78.763%. These values have met the requirements set out in the 2006 Special Lasbutag specifications.